Comparative Analysis Of Investment Return Calculations Between Single Index Model (SIM), Capital Asset Pricing Model (CAPM), And Arbitrage Pricing Theory (APT) In 8 Mining Company Sectors - Dinda Noviani; Dayan Hakim Natigor Sipahutar; Yoyo Sudaryo; Nunung Ayu Sofiati; Tjipto Sajekti (Green Publisher Indonesia, 2024)
This study aims to analyze the comparative calculation of investment return rates between three models, namely Single Index Model (SIM), Capital Asset Pricing Model (CAPM), and Arbitrage Pricing Theory (APT), in eight mining company sectors listed on the Indonesia Stock Exchange (IDX 30). This study uses historical data from the mining company sectors to calculate and compare the investment return rates based on these three models. The research method used is statistical analysis to evaluate and compare the predicted investment return rates from the Single Index Model (SIM), Capital Asset Pricing Model (CAPM), and Arbitrage Pricing Theory (APT). The data used includes historical stock prices, company financial data, and relevant market data. The results of this study are expected to provide a better understanding of the effectiveness and advantages of each model in the context of mining companies listed on IDX 30. The results of this study show that the Single Index Model (SIM) indicates a moderate financial potential with an average value of 7,58, which is lower compared to CAPM. A high risk (beta) of 2,20 indicates that this investment has a higher risk than the market. On the other hand, the Capital Asset Pricing Model (CAPM) has a higher average return value of 19,15, indicating greater profit potential but also commensurate risk. The Arbitrage Pricing Theory calculation of 6,46, the lowest, reflects a more cautious calculation of return estimates. The inflation beta risk value of 100.924,50 and the deposit interest beta risk of 9.320,14 are very high.